2021
DOI: 10.1002/jctb.6921
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of the methanization of the byproducts from OFMSW fermentation

Abstract: BACKGROUND During anaerobic digestion of wastes, volatile fatty acid (VFA) production has been studied, but little attention has been paid to alcohols and lactic acid. Thermodynamically, lactic acid and alcohols are better substrates to produce methane than other VFA. This research identified the metabolites produced during the fermentation of the organic fraction of municipal solid waste and studied their methanization in a second stage. Analysis of the methane production curves is provided and explained acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Also this can be explained by VFA production, more in particular by the production of propionic acid (Angelidaki et al 1999;Siegert & Banks 2005;Wang et al 2009;Ma et al 2011; Jojoa-Unigarro & González-Martínez 2022). For example, at a Sta/Gel ratio of 5.5 a maximum propionate concentration of 1.73 g COD L À1 was measured (Table S2 in.SI), which exceeds propionate concentrations of 0.7-1.5 g COD L À1 that are reported to inhibit methanogenesis (Wang et al 2009;Ma et al 2011;Jojoa-Unigarro & González-Martínez 2022). This can be explained by the high concentration of propionic acid, which results in an increase of partial hydrogen pressure and subsequent inhibition of the overall acetogenesis and consequently, the hydrogenotrophic methanization ( Jojoa-Unigarro & González-Martínez 2022).…”
Section: Effect Of Sta/gel Ratio On Process Ratesmentioning
confidence: 93%
“…Also this can be explained by VFA production, more in particular by the production of propionic acid (Angelidaki et al 1999;Siegert & Banks 2005;Wang et al 2009;Ma et al 2011; Jojoa-Unigarro & González-Martínez 2022). For example, at a Sta/Gel ratio of 5.5 a maximum propionate concentration of 1.73 g COD L À1 was measured (Table S2 in.SI), which exceeds propionate concentrations of 0.7-1.5 g COD L À1 that are reported to inhibit methanogenesis (Wang et al 2009;Ma et al 2011;Jojoa-Unigarro & González-Martínez 2022). This can be explained by the high concentration of propionic acid, which results in an increase of partial hydrogen pressure and subsequent inhibition of the overall acetogenesis and consequently, the hydrogenotrophic methanization ( Jojoa-Unigarro & González-Martínez 2022).…”
Section: Effect Of Sta/gel Ratio On Process Ratesmentioning
confidence: 93%
“…They showed that co-digestion of food waste with a small amount of microalgae biomass results in process stability and increasing methane production. Jojoa-Unigarro and González Martínez 20 presented a comprehensive kinetic study of the methane production from the fermentation byproducts of organic fraction of municipal solid wastes. The impact of steam explosion pretreatment on coffee husks was evaluated by Fonseca et al 21 finding significant improvements on methane production from this important residue generated in many regions of Latin America.…”
mentioning
confidence: 99%